Historical outlines from sound to text - Brinton, Laurel J.; Bergs, Alexander (History of English, 2017)
This series of books reprints articles from the successful English Historical Linguistics: An International Handbook (HSK 34.1 and 34.2) in a convenient paperback set suitable for use in the classroom or by scholars. While the first volume provides an overview of the history of English, the second to fourth volumes focus on individual periods and the final volume covers language variation from an historical perspective.